2021
DOI: 10.3390/ijerph182111493
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Promoting Prefabrication Implementation in Construction Industry towards Sustainability

Abstract: As a game-changing technology with significant environmental, economic, and social benefits, prefabricated technology has attracted attention and has been increasingly adopted in the construction industry. Although multitudinous studies have investigated various aspects of prefabrication in construction, a thorough review of its current development state that synthesized environmental, economic, and social sustainability dimensions remains overdue. Therefore, this study aims to fill this research gap by constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 156 publications
(213 reference statements)
0
15
0
Order By: Relevance
“…Liu et al. (2021) and Wu et al. (2021) conducted bibliographic analyses and highlighted WoS as a preferred choice for review studies in the OSC field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al. (2021) and Wu et al. (2021) conducted bibliographic analyses and highlighted WoS as a preferred choice for review studies in the OSC field.…”
Section: Methodsmentioning
confidence: 99%
“…WoS like Scopus is a digital bibliographic platform that is widely recognised for highquality standards and a common tool for performing bibliometric research relating to construction. Liu et al (2021) and Wu et al (2021) conducted bibliographic analyses and highlighted WoS as a preferred choice for review studies in the OSC field. Similarly, recent literature review studies (Cavalieri et al, 2021;Suchek et al, 2021) in CE research have also used the WoS database.…”
Section: Data Collectionmentioning
confidence: 99%
“…When it comes to material use and environmental impacts prefabrication or offsite construction is seen as more sustainable than traditional methods [39]. Another study [40] also reported that as a game-changing technology with lots of economic, social, and environmental benefits, prefabricated technology has attracted attention and has seen increasing adoption in the construction industry. Although it has been reported that as an alternative construction method, offsite construction (OSC) has a variety of benefits, there is a lack of critical review of the performance of the offsite built facilities in terms of energy consumption and carbon emissions [37].…”
Section: Arguments On the Move Toward Industrialized Buildingsmentioning
confidence: 99%
“…Prefabrication plays a huge part in reducing waste. Studies show that prefabrication can reduce waste on average by up to 50% [25]. From efficient designs that can print foundations and walls without forming or waste from cutting materials to size, printing and using the exact number of materials is a strength of printing homes.…”
Section: Sustainability With 3d Printed Homesmentioning
confidence: 99%